The Relevance of Commendable Attitudes and Actions Standards to the Commutation of the Death Penalty in Indonesia's Criminal Code - Adhim, Muhammad Iqbal Maulana; Erny Herlin Setyorin (LPPM Sekolah Tinggi Ilmu Ekonomi 45 Mataram, 2025)
One of the important updates in the National Criminal Code is the implementation of the conditional death penalty, which provides an opportunity for death row inmates to change their sentence to life imprisonment if they show commendable attitudes and actions during the probation period. The study found that the phrase